Orosomucoid 2 inhibits tumor metastasis and is upregulated by CCAAT/enhancer binding protein β in hepatocellular carcinomas - Fang, Tao (Oncotarget, 2015)
Cancer metastasis is a complex process, and the incidence of metastasis is influenced by many biological factors. Orosomucoid 2 (ORM2) is an important glycoprotein that is mainly biosynthesized and secreted by hepatocytes. As an acute-phase protein, ORM2 likely plays important roles in anti-inflammation, immunomodulation and drug delivery. However, little is known regarding the function of ORM2 in hepatocellular carcinoma (HCC). In this study, we determined that ORM2 expression in HCC tissues was negatively associated with intrahepatic metastasis and histological grade. Moreover, the ectopic overexpression of ORM2 decreased HCC cell migration and invasion in vitro and intrahepatic metastasis in vivo, whereas silencing ORM2 expression resulted in increased tumor cell migration and invasion in vitro. The CCAAT/enhancer binding protein β (C/EBPβ) upregulated ORM2 expression, while only the LAP1/2 (C/EBPβ isoforms) possessed transcription-promoting activity on the ORM2 promoter. Subsequently, we found that LAP1 repressed HCC cell migration and invasion via the induction of ORM2 expression. Consistently, the protein expression of C/EBPβ was negatively associated with histological grade and positively correlated with ORM2 protein expression in HCC tissues. Collectively, our findings indicate that ORM2 is a functional downstream target of C/EBPβ and functions as a tumor suppressor in HCC.